'Transportation' problem of time-optimal heating. (10th April 2007) - Pleshivtseva, Yulia
Induction static heating installations are currently in considerable use in leading industries. The potential of the optimal control theory applied to the steady-state modes optimisation for induction static heaters is considered in this paper, taking into account the transfer stage. The general time-optimal problems statement is discussed from the standpoint of the optimal control theory. Particular optimal control problem formulations and methods to determine the control inputs which satisfy the technological constraints are also provided in this paper. Special optimal control techniques have been developed to solve such problems. The optimisation examples presented prove that optimal control methods can be effectively used for the optimisation of static induction heaters in the forging industry to obtain cost-effective, high quality results.